Influencia del umbral lingüístico en la competencia lectora en estudiantes de educación superior - Sumari, Regina (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a thesis presented at the National University of the Altiplano. The objective of the research was to evaluate the influence of the linguistic threshold on the reading competence of bilingual students. The study was carried out with two groups of 27 Castilian-Quechua and Quechua-Castilian second grade secondary school students from INA 21 in Azángaro, using a quantitative approach, explanatory research type and quasi-experimental design with entry and exit test. The linguistic threshold was determined through receptive and productive vocabulary tests, after a reading reinforcement program; reading competence, through the reading tests of the Ministry of Education; and the relationship between linguistic threshold and reading competence, through Pearson's correlation (r). The results indicate that all the variables evaluated were significant (p < 0.05). The linguistic threshold of the Spanish-Quechua group was higher than that of the Quechua-Spanish group, at an advanced level vs. beginner, a receptive vocabulary of 2130 vs. 975 of the 3000 most frequent words, and a lexical coverage of 71.0 vs. 32.5%, respectively. The reading competence of the Spanish-Quechua group was higher than that of the Quechua-Spanish group, with a score of 718 (satisfactory) vs. 594 (in process), respectively. The correlation between the linguistic threshold and reading competence was high (r = 0.76) and significant (p < 0.05), showing causality and direct positive association between the variables. Based on the results, it is concluded that the linguistic threshold positively influences the reading competence of bilingual Spanish-Quechua and Quechua-Spanish students, showing a significant gap in the achievement of their learning.